2018
DOI: 10.5812/archcid.58976
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antifungal Susceptibility Testing of Clinical and Environmental Fusarium Isolates in Iran

Abstract: Background: Members of the genus Fusarium are common soil saprophytes and important plant pathogens which also cause a wide spectrum of diseases ranging from onychomycosis to the life -threatening systemic infections. The antifungal susceptibility patterns of Fusarium isolates varies in different species. Objectives: This study was undertaken to investigate the antifungal susceptibility pattern of environmental and clinical Fusarium isolates to conventionally -used azole antifungal drugs in Iran. Methods: A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
(47 reference statements)
2
6
0
Order By: Relevance
“…Based on the obtained results, although F. proliferatum was sensitive to two new imidazole and amphotericin B, all F. proliferatum samples were resistant to other antifungal agents. Eventually, the obtained results approved the reports of other researches on low activity of itraconazole and voriconazole against F. proliferatum 17,28,43 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Based on the obtained results, although F. proliferatum was sensitive to two new imidazole and amphotericin B, all F. proliferatum samples were resistant to other antifungal agents. Eventually, the obtained results approved the reports of other researches on low activity of itraconazole and voriconazole against F. proliferatum 17,28,43 …”
Section: Discussionsupporting
confidence: 83%
“…Eventually, the obtained results approved the reports of other researches on low activity of itraconazole and voriconazole against F. proliferatum. 17,28,43…”
Section: Discussionmentioning
confidence: 99%
“…1,26,37 Available data on fungal keratitis in Brazil are scarce and have mainly been collected from regions with humid subtropical climate. [14][15][16][17][18][19][20][21][22] Given the vast territorial dimension of Brazil, with diverse biomes, climates, as well as social and populational singularities, understanding the clinical and etiological characteristics of fungal keratitis at a regional level A study conducted by Ibrahim et al, 38 analysing the prescription and sale of topical ocular natamycin and amphotericin over 6 years in Brazil, revealed that the periods with the highest commercialization of these drugs coincided with months of lower relative humidity.…”
Section: Discussionmentioning
confidence: 99%
“…51 However, previous studies have shown variations in antifungal susceptibility among isolates of Fusarium within the same species complex. 14,19 Although breakpoints have not been described for Fusarium, associated with better outcomes as reepithelialization occurs more rapidly in these cases. 28 According to Oechsler et al, 19 isolates with higher MIC values are more challenging to treat and take longer to respond to therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation